The use of supplementary materials in ESOL classes: A comparative analysis of public and private high schools. - Bravo Garzón, Jovany Santiago (2012)
The present study aims to establish the variety of supplementary teaching materials that ESL instructors utilize in public and private institutions to diversify and boost up class expositions in order to improve learners’ understanding. A comparison on the variety of the supporting materials employed in classes will be determined in both establishments to determine their incidence. Two high schools in the New York City area served for the investigation. Students and teachers from freshman, sophomore and junior high school grades from both establishments were selected to carry out the analysis.